Tantangan Ekonomi terhadap Partisipasi Orang Muda Katolik di Lingkungan Bitauni Paroki Santa Maria Pengantara Segala Rahmat Kiupukan - Videl Remus Kono; Elmagondulfa Habu Lelo; Paulus Pedro Langoday; Libertha Monemnasi; Anastasia Mayang Mota (PASCERE: Jurnal Pengabdian kepada Masyarakat, 2025)
This Community Service Activity aims to increase the understanding of Catholic Youth in the context of the challenge economy and challenge them to participate in the environment of Bitauni Parish, Santa Maria Intercessor of All Graces, Kiupukan. This devotion was implemented based on the results of a previous study, using the method of Participatory Action Research (PAR) in the form of socialization. The evaluation method used for the activity is a pre-test and post-test for 60 Catholic Youth in the Environment Bitauni. Activity results socialization related challenge economy to participation of Catholic Youth, it is said successful and capable answer objective activity Community Service said, the thing. This shows that with increasing understanding of Catholic Youth to challenges that occur, the emergence of motivation and enthusiasm, as well as existing commitment to participate or be involved in various forms of Activities in the Church and Society. Indicators of success can be seen from improved understanding of Catholic Youth after follow-up activity socialization with improved post-test results compared to understanding early Catholic Youth from pre-test results. Successful activity is also marked by thorough planning, good communication, and collaboration?? among the parties involved. Recommendations from the activity This The parish priest, especially the moderator of Young Catholics, needs to design activities involving Catholic Youth. In addition, it is necessary to exist training and empowerment economy and collaboration as well as communication between the Catholic Youth Administrator environment with Catholic Youth parish and the Catholic Youth environment with others. Young Catholics are also expected For not only aware but also committed to participate more real. Keywords : Challenges? Economy , Participation , Catholic Youth , Socialization , Service to Society